Strategi Komunikasi Islami Yang Efektif Dalam Mengatasi Konten Tarian Viral Muslimah di Media Sosial Tiktok (Perspektif Q.S Al-Ahzab Ayat 33) - Riska; Oriza, Lalandra; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The development of information technology and social media, particularly TikTok, has brought new challenges for Muslim women in maintaining their identity and Islamic values. This study explores effective Islamic communication strategies to address viral dance content that often contradicts Islamic teachings, using the perspective of Q.S Al-Ahzab verse 33 as a foundation. The method used is qualitative with a literature study approach, involving collecting data from various sources to support the analysis. The results of the study indicate that viral dance content can influence the image of Muslim women and pose challenges to modesty and aurat. Therefore, wise, educational, and value-based communication strategies are essential to provide a better understanding to the younger generation. The conclusion of this study emphasizes the importance of persuasive and constructive communication approaches, as well as the role of religious figures and influencers in conveying messages that align with Islamic teachings. This research is expected to contribute to the development of relevant communication strategies in the digital era.